2014
DOI: 10.4161/15384101.2014.982941
|View full text |Cite
|
Sign up to set email alerts
|

2-Arachidonoylglycerol enhances platelet formation from human megakaryoblasts

Abstract: Platelets modulate vascular system integrity, and their loss is critical in haematological pathologies and after chemotherapy. Therefore, identification of molecules enhancing platelet production would be useful to counteract thrombocytopenia. We have previously shown that 2-arachidonoylglycerol (2-AG) acts as a true agonist of platelets, as well as it commits erythroid precursors toward the megakaryocytic lineage. Against this background, we sought to further interrogate the role of 2-AG in megakaryocyte/plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 71 publications
1
11
0
Order By: Relevance
“…In addition, PPAR-alpha and -gamma targets mediate NAE anti-inflammatory properties [14]. In particular, in contrast to 2AG, which is involved in immune cell recruitment, AEA suppresses pro-inflammatory cytokines production and enhances the release of anti-inflammatory cytokines regulating the immune responses [15][16][17]. Furthermore, PEA was shown to counteract systemic inflammation in mice and humans [14] and to support the increased intestinal permeability associated with inflammation along with OEA [18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PPAR-alpha and -gamma targets mediate NAE anti-inflammatory properties [14]. In particular, in contrast to 2AG, which is involved in immune cell recruitment, AEA suppresses pro-inflammatory cytokines production and enhances the release of anti-inflammatory cytokines regulating the immune responses [15][16][17]. Furthermore, PEA was shown to counteract systemic inflammation in mice and humans [14] and to support the increased intestinal permeability associated with inflammation along with OEA [18].…”
Section: Introductionmentioning
confidence: 99%
“…The effects occur through CB2 activation (666,866). Furthermore, 2-AG is able to drive a cell line expressing surface antigens of both erythroid and megakaryocytic phenotypes towards megakaryocytic differentiation (128), thereby stimulating platelet production and release (285). Accordingly, 2-AG hydrolytic enzymes are under control of inducers of megakaryocyte differentiation (285).…”
Section: Immune Systemmentioning
confidence: 99%
“…Looking first at the effects of endocannabinoids and endocannabinoid-like compounds on the formation of blood cellular components, AEA, 2-AG and PEA have been shown to stimulate mouse haematopoietic cell growth and differentiation into granulocyte, erythrocyte, macrophage and megakaryocyte colonies (Valk et al 1997;Patinkin et al 2008) through activation of the CB 2 receptor (Valk et al 1997). 2-AG can also increase the formation and maturation of platelets from human megakaryoblasts (Gasperi et al 2014).…”
Section: Endocannabinoids and Bloodmentioning
confidence: 99%
“…The collective results suggested that the potency of AEA in the suppression of IL-2 secretion correlated with levels of COX-2 protein in T cells and that the 2-AG-mediated inhibition of IL-2 secretion was dependent upon COX-2-catalyzed metabolism. Gasperi et al (2014) found that 2-AG was able to initiate and complete the leukocyte adhesion cascade, by modulating the expression of selectins, cell adhesion molecules that are involved in lymphocyte homing and in chronic and acute inflammatory processes. A short exposure of primary human umbilical vein endothelial cells (HUVECs) to 2-AG was sufficient to prime them toward an activated state.…”
Section: Lymphocytesmentioning
confidence: 99%
See 1 more Smart Citation